Meningkatkan kemampuan kompetensi strategis matematis dan kemandirian belajar melalui metode thinking aloud pair problem solving - Silvia Ratnasari; Widya Dwiyanti; Ilfa Febriana; Anton Nasrullah; Sarah Caesarani (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This study aims to determine the effectiveness of the Thinking Aloud Pair Problem Solving (TAPPS) method in increasing strategic mathematics competence and independent learning for high school students compared to the discovery learning method. The experimental method obtained the TAPPS method consisting of 31 students in class X IPA 2 and 31 students in class X IPA 1 received the Discovery Learning method. Data analysis included descriptive statistics, Mann Whitney test and content analysis in the Thinking Aloud Pair Problem Solving method and a scale of attitudes towards learning independence. The results showed that students who received the TAPPS method had a better increase in strategic mathematical competence and independent learning than students who received the Discovery Learning method. The TAPPS method encourages critical thinking, creativity, and active participation in group discussions, increasing confidence in solving math problems.